The painful lives of Pakistani tribal women: A postcolonial feminist reading of Jamil Ahmad’s The Wandering Falcon - Alhourani, Mohammad Issa; Asif, Muhammad; Abouelnour, Moustafa Mohamed; Al Mahamed, Ahmad Mohammad; Abou Adel, Mohamad (Research Journal in Advanced Humanities, 2025)
Jamil Ahmad in his novel The Wandering Falcon narrates the miserable lives of tribal women in Pakistan. The novel depicts the violations of women’s rights in the region and the absence of law to protect and secure the fundamental rights of women. This article aims to provide a textual analysis of The Wandering Falcon in the light of postcolonial feminist theory. The discussion concludes that the female characters in Ahmad’s novel show agency in contrast to the radical and liberal feminist view of third-world women as passive and submissive. Moreover, the study confirms the postcolonial feminist standpoint that women in colonial countries face double oppression at the hands of patriarchy and colonialism. The study identifies the absence of a voice for tribal women’s rights in the mainstream feminist movement in Pakistan. Therefore, this study recommends raising awareness about tribal women’s rights at both local and national levels. The study also appreciates the government’s step to bring the tribal areas under judicial control and it is hoped that it will prove a game-changer for the local tribal women.